Collective Rural Women Access, Use, and Control Over Communal Land in Mexico: A Post-capitalist Feminist Political Ecology Approach - Soto-Alarcón, Jozelin María; González-Gómez, Diana Xóchitl (Frontiers in Sustainable Food Systems, 2021)
Rural women's access to land is fundamental for their individual and household well-being, equity, and empowerment. In Mexico, the agrarian reform of 1992 and customary gendered rights shaped land use, access, and control. The rural women's access to collective land is relevant since social property—ejido and agrarian communities—represents 52% of the national territory. As an expression of the collective organization, commons were also performed to use and control communal land and biophysical resources collectively. This paper examines the collective peasant women's bargaining process to access, use, and control communal land. The post-capitalist feminist political ecology approach allowed us to distinguish and analyze gendered strategies employed by a women-led cooperative at different levels: household, community, and government to access and use communal land and biophysical resources by the process of commons—commoning. Rural women's collective efforts are located in Hidalgo, central Mexico. First, the Agrarian Reform modifications related to gender equality issues are investigated, followed by examining rural women's socioeconomic conditions. The case study permitted us to identify and analyze critical factors that enhanced long-term agreements to control communal land beyond the Agrarian Law scope by the commoning examination. The collective rural women's strategies to use communal land improved well-being based on gendered peasant knowledge, organization, and stakeholder support. Nevertheless, the strategies increased women's burden and reinforced existing gendered norms such as female altruism. Furthermore, it is argued the need to discuss the bargaining process over communal land concerning a diversity of commons: knowledge, social, and biophysical, in which gender and care are critical variables.